Analisis Trend dan Perwilayahan Komoditas Mangga Di Kabupaten Indramayu Jawa Barat - Juri Juswadi; Pandu Sumarna (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2021)
This study aims to identify the trend of production and harvested area of mango and identify the sub-districts of the mango commodity base and the characteristics of its distribution in Indramayu Regency in the period 2009-2019. The research data is secondary data that is time series in the period 2009-2019. Data analysis used LQ (location quotient), localization coefficient, and specialization coefficient. The results of the study in 31 sub-districts showed a declining trend of mango production in most of the sub-districts, only six sub-districts showed an increasing trend of mango production, and 10 sub-districts showed an increasing trend of harvested area. The mango commodity base sub-district is located in 17 sub-districts. Mango cultivation is not concentrated in one or several sub-districts but spreads to all sub-districts and there is no sub-district that specializes in mango production but there is a diversity of cultivation of various fruits in all sub-districts in Indramayu Regency.